Influence of primary tumour and patient factors on survival in patients undergoing curative resection and treatment for liver metastases from colorectal cancer. Issue 1 (3rd February 2020) - Scherman, P.; Syk, I.; Holmberg, E.; Naredi, P.; Rizell, M.
Graphical Abstract: Abstract: Background: Resection of the primary tumour is a prerequisite for cure in patients with colorectal cancer, but hepatic metastasectomy has been used increasingly with curative intent. This national registry study examined prognostic factors for radically treated primary tumours, including the subgroup of patients undergoing liver metastasectomy. Methods: Patients who had radical resection of primary colorectal cancer in 2009–2013 were identified in a population-based Swedish colorectal registry and cross-checked in a registry of liver tumours. Data on primary tumour and patient characteristics were extracted and prognostic impact was analysed. Results: Radical resection was registered in 20 853 patients; in 38·7 per cent of those registered with liver metastases, surgery or ablation was performed. The age-standardized relative 5-year survival rate after radical resection of colorectal cancer was 80·9 (95 per cent c.i. 80·2 to 81·6) per cent, and the rate after surgery for colorectal liver metastases was 49·6 (46·0 to 53·2) per cent. Multivariable analysis identified lymph node status, multiple sites of metastasis, high ASA grade and postoperative complications after resection of the primary tumour as strong risk factors after primary resection and following subsequent liver resection or ablation. Age, sex and primary tumour location had no prognostic impact on mortality after liver resection. Conclusion: Lymph node status and complications have a negative impact on outcome after both primary resection and liver surgery. Older age and female sex were underrepresented in the liver surgical cohort, but these factors did not influence prognosis significantly.